DASAR KEBUTUHAN PENGEMBANGAN ASESMEN ALTERNATIF MODEL PEMBELAJARAN STEM UNTUK KELOMPOK B SUB TEMA BENDA-BENDA ALAM - Widyastuti, Windi; Mulyana, Edi Hendri; Rahman, Taopik (Universitas Pendidikan Indonesia (UPI), 2021)
The current demand for education in Indonesia is to develop 21st century skills which are often called 4C skills which consist of Critical Thinking, Creativity, Communication, and Collaboration. One of the lessons that are suitable for developing 4C skills is STEM-based learning. STEM-based learning is learning that combines four disciplines, namely Science, Technology, Engineering, and Mathematics. By using STEM-based learning, children will be brought closer to real situations in everyday life. In addition to learning models, assessment is one component of education. Assessment is a process of analyzing information about the achievements of students both in the process and learning outcomes. However, in reality, some educators do not fully understand how to conduct an assessment. Therefore, in this article, the author provides information about the basic needs for assessment of alternative STEM learning models for group students on the sub-theme of natural objects. The method used by the researcher is the development of the Educational Design Research design. The author realizes that the assessment carried out by the teacher is still subjective and has not been carried out optimally, nor is there an alternative assessment rubric for the STEM learning model. Teachers also do not understand the STEM learning model and have not been able to develop their own assessment rubric.Tuntutan pendidikan di Indonesia saat ini yaitu mengembangkan keterampilan abad 21 yang sering disebut juga keterampilan 4C yang terdiri atas Critical Thinking, Creativity, Communication, and Collaboration. Salah satu pembelajaran yang cocok digunakan untuk mengembangan keterampilan 4C ialah pembelajaran berbasis STEM. Model pembelajaran STEM merupakan pembelajaran yang menggabungkan empat disipIin iImu yaitu Science, Technology, Engineering, dan Mathematic. Dengan menggunakan pembelajaran berbasis STEM anak akan didekatkan dengan situasi nyata dalam kehidupan sehari-hari. Selain model pembelajaran, asesmen merupakan salah satu komponen pendidikan. Asesmen merupakan seraingkan proses mengolas informasi mengenai capaian peserta didik baik dalam proses maupun hasil belajar. Namun pada kenyataannya sebagian pendidik belum sepenuhnya mengerti bagaimana seharusnya melakukan penilaian. Maka dari itu dalam artikel ini penulis memberikan informasi mengenai dasar kebutuh asesmen alternatif model pembelajaran STEM untuk peserta didik kelompok pada sub tema benda-benda alam. Metode yang digunakan peniliti yaitu pengembangan dengan desain Educational Design Research. Penulis menyadari bahwa penilaian yang dilakukan oleh guru masih bersifat subjektif dan belum terlaksana secara optimal, juga belum tersedianya rubrik asesmen alternatif pada model pembelajaran STEM. Guru juga belum memahami model pembelajaran STEM dan belum dapat mengembangkan rubrik asesmen sendiri.